Serum neurofilament light chain is a biomarker of human spinal cord injury severity and outcome. Issue 3 (16th June 2014) - Kuhle, Jens; Gaiottino, Johanna; Leppert, David; Petzold, Axel; Bestwick, Jonathan P; Malaspina, Andrea; Lu, Ching-Hua; Dobson, Ruth; Disanto, Giulio; Norgren, Niklas; Nissim, Ahuva; Kappos, Ludwig; et al.
Abstract : Background: Neurofilaments (Nf) are major structural proteins that occur exclusively in neurons. In spinal cord injury (SCI), the severity of disease is quantified by clinical measures that have limited sensitivity and reliability, and no blood-based biomarker has been established to further stratify the degree of injury. We aimed to examine a serum-based NfL immunoassay as predictor of the clinical outcome in SCI. Methods: Longitudinal measurement of serum NfL was performed in patients with central cord syndrome (CCS, n=4), motor-incomplete SCI (iSCI, n=10), motor-complete SCI (cSCI, n=13) and healthy controls (HC, n=67), and correlated with clinical severity, neurological outcome, and neuroprotective effect of the drug minocycline. Results: Baseline NfL levels were higher in iSCI (21 pg/mL) and cSCI (70 pg/mL) than in HC (5 pg/mL, p=0.006 and p<0.001) and CCS (6 pg/mL, p=0.025 and p=0.010). Levels increased over time (p<0.001) and remained higher in cSCI versus iSCI (p=0.011) and than in CCS (p<0.001). NfL levels correlated with American Spinal Injury Association (ASIA) motor score at baseline (r=−0.53, p=0.004) and after 24 h (r=−0.69, p<0.001) and 3–12-month motor outcome (baseline NfL: r=−0.43, p=0.026 and 24 h NfL: r=−0.72, p<0.001). Minocycline treatment showed decreased NfL levels in the subgroup of cSCI patients. Conclusions: Serum NfL concentrations in SCI patients show a close correlation with acute severity and neurological outcome. Our data provide evidence that serum NfL is of prognostic value in SCI patients for the first time. Further, blood NfL levels may qualify as drug response markers in SCI.